Vertical aerosol profiles and the impact of regional transport in a background region of Northwest China: Insights from ground-based lidar - Kai Cheng; Xia Li; Yaqiong Kuang; Yuting Zhong; Haiyang Cai; Shuting Li (Atmospheric Research, 2026)

First report of a carbapenemase gene blaOXA-181 harbored in a conjugative plasmid in Kluyvera sichuanensis isolated from spinach - Xu Yang; Jinkyung Kim; Nhu-Y Do; Xinhui Li; En Huang; Se-Ran Jun; Sun Hee Moon; Erin L. DiCaprio; Shuting Chen (International Journal of Food Microbiology, 2026)

Sulfur vacancy engineering in Bi2S3 nanorods boosts piezocatalytic molecular oxygen activation for efficient pollutant degradation - Jiangdong Dai; Ziyi Liu; Shuting Liu; Chenxiao Yu; Qiaoyu Gao; Wenhua Xue; Dongyi Li; Lulu Wang; Xiaohui Dai; Xiaohua Tian; Yanhua Cui; Jian Ye (Journal of Environmental Chemical Engineering, 2026)

Effects of localized heating body segments on the effectiveness of personal comfort systems in cold environments: A meta-analysis - Longde Chen; Kun Zhou; Shuting Li; Yankai Zhao; Hao Chen; Yi Xu (Energy and Buildings, 2026)

Dual-responsive and CD44-targeted nanotherapy to remodel the fibrotic niche for reversing liver fibrosis - Jingwei Li; Jiahao Chen; Lingling Wang; Wei Zhao; Yan Xia; Jinhang Zhang; Jie Zhou; Haiying Song; Xinghe Ji; Zijing Zhang; Shuting Qiu; Xiandan Jing; et al. (Chemical Engineering Journal, 2026)

A fish-skin-inspired wearable scale-ionogel composite for impact protection and motion sensing - Tianyu Xu; Zimu Li; Lin Mei; Hanshen Huang; Jie Tian; Zijian Mei; Shuting Liu; Xiaoming Liu; Xinglong Gong; Tianzhi Luo (Chemical Engineering Journal, 2026)

Water‑flow‑induced piezoelectric polarization and nitrogen self‑doping in interpenetrating membranes for efficient hydrogen evolution - Yanhua Cui; Shuting Liu; Zengkai Wang; Chunyan Li; Weilong Shi; Jian Ye (Process Safety and Environmental Protection, 2026)

Enhanced volatile fatty acids production from anaerobic co-fermentation of waste activated sludge and food waste via electrochemical pretreatment: Performance of carbon source utilization, safety and economic analysis - Qingshan Lin; Lihong Wang; Kejie He; Li Li; Shuting Liang; Yeqing Li; Zichong Zhu; Gang Guo (Journal of Water Process Engineering, 2026)

Comprehensive analyses of carbapenem-resistant and ESBL-producing bacteria in fresh vegetables and their resistome in the United States - Sun Hee Moon; Xu Yang; Jinkyung Kim; Elizabeth Leighton; Se-Ran Jun; Erin DiCaprio; Chelsea Gale; Shuting Chen; Xinhui Li; En Huang (Food Research International, 2026)

Diverse crop rotation promoted crop yield via microbial networks in North China Plain - Shuting Yu; Yubin Zhao; Tianshu Wang; Shuihong Yao; Yang Gao; Jun Li; Xinhua Peng; Bin Zhang (European Journal of Agronomy, 2026)

Hierarchical hemispheres microstructure-based iontronic pressure sensor with high sensitivity and wide linear range for gait analysis - Xiaohui Guo; Hao Guo; Bing Hu; Yunjie Peng; Chuanwen Li; Shuting Cao; Junhao Li; Honglin Chen; Zhiyuan Liu; Ming Hou; Ting-Jung Lin; Yunong Zhao; et al. (Chemical Engineering Journal, 2026)

Integrated biological sulfidogenic process: Synergizing sulfate and elemental sulfur reduction for metal-laden wastewater treatment - Jiahua Guo; Junjie Han; Chenxin Zhang; Hao Li; Cheng Li; Shuting Chen; Yibo Wang; Yu Li; Feng Jiang (Water Research, 2026)

Activating Na4 site via crystalline-phase-engineering enables charge redistribution and stress mitigation in Na4Fe3(PO4)2P2O7 cathodes - Linlin Zhou; Danjing Yang; Shuting Wen; Ling Chen; Chenwei Li; Haifeng Yu; Hao Jiang; Chunzhong Li (Science Bulletin, 2026)

Sequential expression of heat shock proteins 70 contributing to the heat response of Haemaphysalis longicornis (Acari: Ixodidae) - Jinrong Gao; Tong Li; Litian Cui; Liwei Wang; Ziqing Ma; Xiaodong Zhang; Jiahe Bai; Yantong Liu; Shiqi Jia; Shuting Wu; Xiaoli Zhang (Journal of Thermal Biology, 2026)

Structural controls of the Shawn gold system, Siguiri district, West Africa: Integrating tectonics, deep drilling and microstructural analysis - Kai Zhang; Shuyun Cao; Yibin Peng; Shuting Wang; Xiaowen Li; Lefan Zhan; Jing Guo (Journal of Structural Geology, 2026)

A Trajectory–Activity Vitality Framework for Neighborhood Open Spaces: Linking Spatial Attributes and Microclimate with Pedestrian Movement and Activity Patterns - Chuancheng LI; Zhiling ZHU; Shuting Yan; Xilin ZHOU (Building and Environment, 2026)

Legume identity shapes soil multifunctionality and microbial networks in long-term cereal-based rotations - Shuting Yu; Shuo Li; Jin Yang; Kees Jan van Groenigen; Guiying Jiang; Mengru Wang; Beibei Wang; Fang Liu; Haitao Liu; Xiaolei Jie; Shiliang Liu (Applied Soil Ecology, 2026)

Targeting IL-33 in Precision Neuroimmunology: Cellular Mechanisms and Therapeutic Strategies for CNS Disorders - Lili Li; Shuting Wang; Lian Duan; Luyu Zhang; Hongmu Yan; Yue Zhu; Luyang Tao; Yuan Gao (Journal of Neuroimmune Pharmacology, 2026)

Influence of beach nourishment on the ecological rehabilitation of sandy beaches: A case study of Beihai Silver Beach on the southern coast of China - Hongshuai Qi; Min Chen; Shuting Zeng; Shunling Wu; Xiaoli Song; Haiqin Duan; Jiayu Li; Feng Cai (Ocean & Coastal Management, 2026)

Temporal dynamics and synergistic pollution of microplastics and heavy metal(loid)s in subtropical mangrove sediments - Shuting Qin; Li Shang; Jiawei Liao; Ismail Khan; Xingyun Huang; Yingwen Li; Lulu Zhang; Faming Wang; Bi Zou; Ping Zhuang (Gondwana Research, 2026)

Self-sacrificial ion-exchange recognition driven ultrasensitive photoelectrochemical sensing of silver ions using a dual Z-scheme WO3@ZnIn2S4/CdS heterojunction - Shuting Wang; Yiting Lei; Huijun Zheng; Gaiping Li; Lina Zou (Analytica Chimica Acta, 2026)

Ecosystem-scale energy balance characteristics in mixed coniferous and broad-leaved forests in southwestern China - Kun Zhao; Yunqi Wang; Lei Ma; Cheng Li; Kai Wang; Xuanwo Liu; Shuting Gong; Xiaodong Niu; Yonglin Zheng; Chuan Jin (Agricultural and Forest Meteorology, 2026)

Mixed exposure to brominated flame retardants adversely affects vaccine-induced antibody titers: Risk prioritization and benchmark dose modeling - Zihui Zhao; Chi Zhang; Xueyu Chen; Yongheng Yan; He Jiao; Xianhao Wang; Ruxu Yan; Yiqian Wang; Meng Liu; Xianfeng Yue; Yuqian Sui; Xia Li; et al. (Toxicology Letters, 2026)

Scoparone alleviates cisplatin-induced acute kidney injury by inhibiting 5-lipoxygenase-mediated ferroptosis - Congcong Dai; Shuting Huang; Na Huang; Suwan Mu; Suwang Liu; Minhui Xie; Jing Mei; Yuhong Tang; Honghao Yu; Pengpeng Yue; Yong Li; Jun Ou (Toxicology and Applied Pharmacology, 2026)

Calcium signaling and hormonal regulation mediate Trichoderma harzianum NDT-1-induced resistance against postharvest gray mold in tomato - Yawen Wang; Zhenshuo Wang; Ruoyu Wu; Shuting Chen; Baojuan Sun; Weijie Xu; Tao Li; Yuyang Zhang; Yanwei Hao; Chao Gong (Postharvest Biology and Technology, 2026)

Rethinking Ship Emission Hotspots: A 100 m Resolution AIS-Based Inventory for Coastal Chinese Waters - Shuting Sun; Huihui Zhao; Xianchao Yang; Li Zhu; Wei Han (Journal of Marine Science and Engineering, 2026)
Existing ship emission inventories for coastal seas are typically gridded at 500 m to 1 km, a resolution too coarse to distinguish navigation channels from anchorage zones. Whether the hotspot patterns reported at such scales reflect true emission geography or are artifacts of spatial averaging remains an open question. We construct a 100 m resolution AIS-based emission inventory for two contrasting coastal environments in eastern China—the Yangtze River estuary and the Wenzhou coastal area—using the STEAM framework, and we quantify spatial concentration with Lorenz curve analyses. At this finer resolution, three emission archetypes become separable: discrete anchorage clusters, bankside berthing bands flanking navigation lanes, and sinuous riverbank traces in confined waterways. Emissions are extremely concentrated: the top 1% of grid cells capture over three-quarters of the total theoretical emission potential (Gini = 0.940), and this pattern persists across all months of 2023. Reaggregating the same data to 1 km reduces the top-1% share by roughly 10%, confirming that coarse gridding systematically understates anchorage contributions while overstating those of transit corridors. A dedicated sensitivity analysis on auxiliary engine load assumptions (±30% perturbation of canonical Jalkanen-style load brackets) shows that, while absolute emission totals carry approximately ±15% uncertainty, the spatial concentration of emissions is highly robust: Across all perturbation scenarios, the Gini coefficient varies by less than 0.01, the top-5% emission share varies by less than 2 percentage points, and the location of top-5% hotspot cells overlaps by ≥97.9% (Jaccard index). The results highlight stationary vessel hotspots—discrete anchorages and bankside berths—as a major and previously underemphasized contributor to the cumulative coastal ship emission budget, complementing rather than replacing the conventional navigation-lane focus, with direct implications for shore power siting, anchorage management, and emission control zone design.

Fabrication of monovalent cation perm-selective membranes via quaternized poly(aryl ether sulfone) modification for efficient Li+/Mg2+ separation - Shuting Zhang; Yunxiang Ouyang; Khalznkhuu Otgonlkhagva; Jiaze Li; Jialin Lv; Na Li; Zhaoxia Hu; Shouwen Chen (Desalination, 2026)

Boosting sensitivity in self-powered visible-blind UV detectors through gradient oxide-semiconductor/perovskite heterostructure - Xuehu Luo; Zhanwei Liu; Junnan Mai; Huasheng Chen; Junpeng Deng; Shuting Cai; Wei Zhong; Sunbing Deng; Guijun Li; Hoi-sing Kwok; Jianfeng Zhang; Yuan Liu (Chemical Engineering Journal, 2026)

The co-assembled hesperidin-emodin nanospindles for synergistic enhancement of regenerative repair in MRSA-infected incisions - Li Chang; Shuting Xie; Pengxiang Xu; Zhoubing Shan; Aidi Tong; Mingbao Luan; Chunyi Tong; Bin Liu (Chemical Engineering Journal, 2026)

A machine learning-based model for soil iron oxides estimation using fused hyperspectral and multispectral data - Yongshi Tan; Zhenxi Wei; Yan Xiao; Yulin Huang; Zongxin Li; Shuting Yang; Lin Zou; Lanhui Yang; Yusong Deng (Journal of Soils and Sediments, 2026)

Myasthenia Gravis patients have reduced DTI-ALPS-Index and gBOLD-CSF coupling, suggesting impaired brain waste clearance - Jianxian Zeng; Shuting Han; Mengying Zhu; Yi Shang; Peng Wu; Qinghua Gu; Yonggang Li (Brain Imaging and Behavior, 2026)

LDH-based avermectin nanopesticide modulates bioaccumulation, antioxidant responses, and microbiota stability in earthworms' gut - Shuting Yang; Yiqiong Li; Chao Zong; Xinglu Pan; Haonan Wang; Qingkui Fang; Linlin Shi; Fengshou Dong; Haiqun Cao (Pesticide Biochemistry and Physiology, 2026)

Dose–dependent effects of ferrous sulfate on carbon–nitrogen stabilization and microbial functional pathways in manure composting - Haili Si; Shuting Tang; Lei Li; Shengbo Wang; Junzhi Chen; Yulong Li; Lidong Ji (Journal of Environmental Management, 2026)

Understanding of a sudden shift from foehn to late spring cold span on the north slope of the Middle Tianshan Mountains with meteorological observation and terrain sensitivity simulation experiments - Maoling Ayitikan; Alaiyi Aiding; Yusufu Musha; Qing He; Chengguang Yang; Wulifan Hanan; Shuting Li; Yuting Zhong; Kai Cheng (Journal of Mountain Science, 2026)

Interactive effects of microplastics, heavy metals, and soil microecology under different irrigation water sources - Rui Yang; Lijuan Huo; Hao Yang; Yan Gong; Gaiqiang Yang; Shuting Tian; Shuhui Cao; Xia Li; Qingwei Ding; Yaqiong Fan; Qi Liu (Applied Soil Ecology, 2026)

Further endeavours are needed to promote nature-based solutions for wildfire management under climate warming - Dongli Yu; Shuting Li; Dongyu Cao; Xinglei Cui (Climate and Development, 2026)

A simple model for long-term prediction of sewage flow in a changing climate - Jingyu Ge; Jiuling Li; Ruihong Qiu; Tao Shi; Shuting Wang; Zi Huang; Zhiguo Yuan (Water Research, 2026)

Long-term assessment of natural mineral-based electrochemical systems for concurrent wastewater treatment and nutrient recovery - Yukun Xing; Shuting Chen; Baile Wu; Xiyuan Feng; Ke Hu; Xiaoxiang Zhang; Junyu Zhou; Jingsheng Shi; Yafei He; Peng Li; Zhengyu Jin (Journal of Water Process Engineering, 2026)

Copper modifies ceramic membrane for catalytic air oxidation of humic acid at low temperatures - Jieyi Gong; Shuting He; Wenjia Huang; Jiabai Cai; Huan Li (Journal of Environmental Sciences, 2026)

Optimized one-step pyrolysis synthesis of zinc-modified sludge biochar for enhanced perfluorooctane sulfonate removal from water - Muzi Li; Ranbin Liu; Xiaodi Hao; Dongye Zhao; Xi Cheng; Jian Pan; Tianyuan Xu; Shuting Tian; Yangmo Zhu (Environmental Research, 2026)

Stability and Transport of Ferrihydrite Nanoparticles in Alkaline Soils - Yan Gong; Meiling Wang; Shuting Tian; Qingwei Ding; Xia Li; Gaiqiang Yang; Qi Liu; Juanfang Yang; Lijuan Huo (Water, Air, & Soil Pollution, 2026)

Classification of key aerosol types from multiple satellite products in Xinjiang, West China - Honglin Pan; Xia Li; Shuting Li; Maoling Ayitikan; Yuting Zhong (Theoretical and Applied Climatology, 2026)

Unbiased Segmentation and Multifeature Classification of Cortical Neuronal Activity Reveals Complex Dynamics Under Anesthesia - Zilin Wang; Ao Li; Guihua Xiao; Xingzheng Gu; Zhilei Wang; Shuting Guo; Rujin Zhang; Chaowei Zhuang; Jiangbei Cao (Neuroscience Bulletin, 2026)
Cortical layer 2/3 plays a pivotal role in regulating perception and consciousness. However, the effects of anesthetic agents on the dynamic activity patterns in this layer remain poorly understood. This study examined how neuronal activity in cortical layer 2/3 dynamically changes under anesthesia. Using high-resolution wide-field microscopy, we performed whole-brain synchronous imaging of layer 2/3 neuronal activity in mice. Using these recordings, we performed an unbiased segmentation of the awake, anesthesia, and recovery stages and classified neurons into three categories according to their activity features. Our findings revealed the characteristics of cortical dynamics under anesthesia, including a rebound effect during recovery and nonlinear changes in neuronal activity. We also confirmed the consistent and uniform characteristics of superficial cortical layer activity under anesthesia. These results increase the understanding of cortical dynamics and provide a theoretical basis for improving clinical monitoring techniques and protocols.

DNA co-recognition and pH dependent regulation mechanism of zinc finger domain and C-terminal basic region of CreA in Aspergillus - Yunbin Jiang; Shuting Lan; Jun Li; Liuyan Cai (Archives of Microbiology, 2026)

Nanoengineering of STING-IDO1 feedback machinery potentiates antitumor immunity - Yanming Xia; Lixin Hu; Xiaohu Wang; Mingxi Li; Bo Shi; Siqi Zhu; Yutong Wu; Shuting Xiang; Lifang Yin; Suxin Li (Chemical Engineering Journal, 2026)

Simultaneous identification and detection of five antibiotics using a machine learning-enhanced glass capillary SERS sensor - Sisi Tang; Ruili Li; Yujun Cheng; Shuting Huang; Qi Liu; Xiaoqing Chen (Journal of Hazardous Materials, 2026)

From perinodular to nodular tissues: aberrant accumulation of ornithine accelerates pulmonary fibrosis in silicosis - Ling Wang; Shuxian Wang; Hongxin Li; Shuting Wei; Yiwei Shi; Xuemei Qin; Zhenyu Li (Journal of Environmental Sciences, 2026)

Evaluation of three scale-aware planetary boundary layer schemes in WRF Model during Beijing 2022 Winter Olympics - Yuhuan Li; Min Chen; Shiguang Miao; Gaojie Zhang; Qianqian Huang; Shuting Zhang (Atmospheric Research, 2026)

Chemical composition, source apportionment and formation mechanisms of PM2.5 in urban and background areas of northwestern China - Kai Cheng; Yuting Zhong; Xinchun Liu; Xia Li; Maulen Ayitken; Shuting Li; Hongna Chen; Bingbing Leng; Wang Zhang; Haiyang Cai (Atmospheric Pollution Research, 2026)

An extra-large panicle gene ELP1 from wild rice Oryza officinalis increases grain number and grain yield - Jiachen Ma; Mei Li; Yanan Lin; Jinjin Lian; Yizhengnan Zhu; Jing Yang; Wenfan Hu; Luyi Zhang; Shuting Li; Weilin Zhang (Theoretical and Applied Genetics, 2026)

Spatiotemporal dynamics of ammonium monooxygenase (amoA) genes in sediments of the aquaculture area in the Yellow Sea Cold Water Mass - Shuting Li; Li Li; Xiangli Tian; Qinfeng Gao; Shuanglin Dong (Regional Studies in Marine Science, 2025)

Overexpression of the cold-repressed StWRKY70 enhances cold-induced sweetening resistance by coordinately attenuating starch-to-sugar conversion and increasing respiratory pathways - Rui Jiang; Chunyan Jiang; Xinyu Ni; Shuting Hu; Xiaoshuang Cui; Danting Li; Hui Sun; Tong Zhou; Jichun Wang; Dianqiu Lv; Xun Liu (Postharvest Biology and Technology, 2025)

Numerical investigation into the unsteady flow characteristics around a fully appended SUBOFF model combined with a pump-jet propulsor - Shuting Cai; Renfang Huang; Ning Li; Yi An; Qiang Wu; Yiwei Wang (Ocean Engineering, 2025)

Multi-parameter fusion-based evaluation of cavitation intensity - Lihua Huang; Qiang Li; Shuting Wan; Jiangyun Wang; Jianxin Liu (Ocean Engineering, 2025)

Effects of hydroxylated silica surface on molecular-scale water freezing with implications for unsaturated permafrost - Shuting Ji; Liang Lei; Sergio Andres Galindo Torres; Ling Li (Journal of Hydrology, 2025)

New insights into the impact of heavy metals on phosphorus recovery: Interaction with the phase transition of CaP precipitation - Xiang Li; Xin Hu; Shuting Shen; Rui Wan; Guo Ting; Xiwu Lu (Journal of Environmental Chemical Engineering, 2025)

Ultra-stable crease-structured paper pressure sensor with ultra-low detection limit for wind sensing and real-time texture recognition - Yugang Chen; Shasha Wang; Yan Li; Mengyu Cao; Xun Fu; Shuting Xie; Jiangtian Tan; Huan Gao; Linghai Xie (Chemical Engineering Journal, 2025)

Paper-based perovskite artificial neuromorphic retina: Flexible sensing-processing architecture with dual-mode encryption - Zhanwei Liu; Jianfeng Zhang; Junnan Mai; Xuehu Luo; Yanting Chen; Yuhao Ruan; Dengyun Lei; Shuting Cai; Yao Ni; Guijun Li; Jing Wang; Qifan Xue; et al. (Chemical Engineering Journal, 2025)

High pressure torsion technology applied to ZnO nanomaterials for enhancing the room-temperature HCl sensing performance - Shuting Wei; Dan Yang; Renquan Guan; Peng Xu; Yuxin Wang; Yingmin Teng; Aicen Li; Junkai Zhang; Huaqiao Tan; Lili Wang; Zheng Lou; Wenjuan Zhang; et al. (Chemical Engineering Journal, 2025)

Effects of different frequencies of transcranial alternating current stimulation on emotion and emotion regulation - Siyuan Zhang; Shuting Yu; Xuebing Li (Cognitive Neurodynamics, 2025)

Radial oxygen loss of Typha latifolia outperforms microbial effects in heavy metal(loid) stabilization - Taicong Liu; Liying Lan; Yuanyuan Li; Daijie Chen; Ming Ao; Shuting Tang; Haojie Qu; Chao Jin; Miaoyue Zhang; Roland Bol; Jean Louis Morel; Zhihong Xu; et al. (Environmental Research, 2025)

Seismic performance of bolt-connected fully assembled concrete modular construction by full-scale shaking table test - Feng Xiong; Dongdong Zhang; Mingming Ran; Wei Li; Guangyun Kou; Shuting Lei (Engineering Structures, 2025)

The influence of emotion on human thermal comfort: based on netted meta-analysis - Kun Zhou; Hao Yang; ShuTing Li; YaYu Feng; TianYi Pang; YanKai Zhao; Yi Xu (Energy and Buildings, 2025)

Biomimetic hydrogel microsphere encapsulated superoxide dismutase enzymes alleviate postoperative peritoneal adhesion by modulating oxidative stress-inflammation cycles via Piezo1 mechanosensitive channels - Shuting Yang; Chao Qu; Xuetao Yuan; Ke Liu; Kai Deng; Jiayin Du; Yuanbo Wang; Man Xu; Li Zhang; Mingzhen Zhang; Ting Liang; Xuqi Li (Chemical Engineering Journal, 2025)

MOF-derived Pt/CeO2 catalysts with N and Zr co-doping for enhanced hydrogen production via aqueous phase reforming of methanol - Songqi Leng; Taizong Shen; Shuting Li; Haoyu Wang; Shahzad Barghi; Dan Wu; Chunbao Charles Xu (Chemical Engineering Journal, 2025)

Synergistic impact of starch-tannic acid complex in regulating gut microbiota to produce propionate - Shuting Duan; Yiming Hu; Xiaowei Zhang; Enpeng Li; Cheng Li (Carbohydrate Polymers, 2025)

Broccoli long non-coding RNA BroNR8 affects salt tolerance by mediating AtWRKY54-related reactive oxygen species homeostasis in Arabidopsis - Hongli Yuan; Shengyi Liu; Shuting Ma; Jiafeng Yu; Di Huang; Ziguang Liu; Shuang Li; Yasushi Yukawa; Juan Wu (Planta, 2025)

Microbial and nematode regulation of Tamarix chinensis growth across successional stages in coastal wetlands - Shuting Li; Jilin Zhang; Yujie Li; Renqing Wang; Peiming Zheng; Hui Wang (Plant and Soil, 2025)

Mechanistic insights into heavy metal adsorption on hydroxyapatite: New perspectives from dynamic adsorption behavior - Shuting Shen; Wenjing Li; Ting Guo; Rui Wan; Xiwu Lu; Hongliang Dai; Xiang Li (Journal of Environmental Chemical Engineering, 2025)

Characterization of microRNAs, phasiRNAs and hc-siRNAs in Citrus sinensis during Candidatus Liberibacter asiaticus infection - Yanan Hu; Nannan Lu; Shuting Liu; Kaiqiang Bao; Ruimin Li; Guiyan Huang (Horticulture, Environment, and Biotechnology, 2025)

Polystyrene Microplastics Induce Insulin Resistance and Glucose Metabolism Disorders in Grass Carp (Ctenopharyngodon idellus) via the Gut Microbiome–Metabolism Axis - Fubin Zhang; Shuting Huang; Xueting Chen; Zhendong Qin; Li Lin (Fishes, 2025)
Polystyrene microplastic (PS-MP) particles disrupt aquatic biological systems due to their persistence and high bioaccumulation potential, causing structural damage and inflammatory responses. PS-MPs also act as metabolic disruptors, affecting glucose metabolism and insulin signaling, although the mechanisms underlying these effects remain unclear. In this study, grass carp were exposed to 100 μg/L and 400 μg/L of polystyrene MPs for 30 days. Histopathological analysis showed the shortening of intestinal villi, vacuolization, and inflammatory infiltration. Antioxidant enzyme activities (SOD and CAT) were reduced, while the presence of tissue damage markers (GPT and GOT) was elevated, suggesting a biphasic oxidative stress response. Transcriptomic analysis revealed downregulation of genes related to metabolism and insulin signaling, especially at 400 μg/L. Gene set enrichment analysis (GSEA) highlighted pathways related to insulin resistance and type 2 diabetes, indicating the disruption of glucose metabolism. Microbiome analysis showed reduced diversity, expansion of Proteobacteria (opportunistic pathogens), and a decrease in beneficial bacteria like Bacillus. These shifts correlated with changes in the expression of key insulin signaling genes, emphasizing the role of host–microbiota interactions in metabolic imbalances. This study revealed that PS-MPs disrupt glucose metabolism and insulin signaling in grass carp through a combination of histological damage, oxidative stress, and microbiota dysbiosis.

Smartphone-integrated visual inspection for enhancing agricultural product quality and safety: a review - Lingyuan Xu; A. M. Abd El-Aty; Peipei Li; Jia Li; Jing Zhao; Xingmei Lei; Song Gao; Yun Zhao; Yongxin She; Fen Jin; Jing Wang; Shuting Wang; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Cognitive experiments on labelling uncertainty for LCZ mapping across heterogeneous megacities in China: Introducing multi-source geospatial data and LCZ subclasses - Xilin Zhou; Jinyang Hu; Shuting Yan; Chuancheng Li (Urban Climate, 2025)

Sensitive and selective simultaneous detection of ampicillin and chloramphenicol in foods with a SERS-activated molecularly imprinted capillary sensor - Sisi Tang; Ruili Li; Shuting Huang; Qi Liu; Xiaoqing Chen (Food Chemistry, 2025)

Crocin alleviates high-sugar diet-induced type 2 diabetes model in Drosophila - Shichao Yu; Xue Lei; Shuting Meng; Xinyan Teng; Guanhua Yue; Jiahua Zhu; Bing Bi; Li Hua Jin (Food Bioscience, 2025)

Impact of marine chlorine emissions on secondary organic aerosols in North China Plain - Zhaoqi Gao; Lin Li; Zhou Liu; Jiangshan Mu; Zhuyi Wang; Bin Luo; Jingzhu Zhang; Shuting Tang; Hongliang Zhang; Jianlin Hu; Xuan Wang; Xuehua Zhou; et al. (Environmental Pollution, 2025)

All-screen-printed tactile sensor for robotic arm via polymeric thermal foaming - Xun Fu; Yugang Chen; Shuting Xie; Mengyu Cao; Qiang Zhao; Yixiao Liu; Yang Li; Shasha Wang; Xiaogang Cheng; Linghai Xie (Chemical Engineering Journal, 2025)

Boosting hydrogen evolution activity of porous NiCo nitrides via modulating d-band center in alkaline seawater electrocatalysis - Tingting Wu; Xiaojing Li; Yifan Li; Shuting Zhang; Wenjiao Chang; Jingqi Chi; Lei Wang (Chemical Engineering Journal, 2025)

Characteristics, sources and risk assessment of volatile organic compounds in a subway environment - A case study in Xi’an, China - Meng Xiu; Yan Cheng; Shuting Liu; Yu Huang; Yonggang Xue; Yan Li; Yanan Meng; Rohan Jayaratne; Xianyu Wang; Phong K. Thai; Alma Lorelei de Jesus; Lidia Morawska (Building and Environment, 2025)

Variations in microbial community structure and extracellular enzyme stoichiometry in heavy metal-contaminated soil under different fertilization regimes - Xian Huang; Shuting Tang; Xiaoming Xin; Lixing Chen; Xinying He; Yueying Huang; Fangming Yu; Yi Li (Applied Soil Ecology, 2025)

Interdecadal response of Eurasian snow water equivalent to sea surface temperatures in the Northern Hemisphere - Xianru Li; Zhigang Wei; Li Ma; Shuting Wu; Kaili Cheng (Journal of Hydrology, 2025)

Natural, tough and pH-responsive ultrasound modified soy protein isolate-arabinoxylan based double network hydrogels for controlled nutrients release - Ran Tao; Gaolin Li; Siyang Wang; Yufeng Sun; Yurui Li; Peiying Wang; Shuting Huang; Bei Fan; Fengzhong Wang (Food Hydrocolloids, 2025)

Self-constrained octahedral distortion for high-performance quasi-2D blue perovskite light-emitting diodes - Zhiqing Zhang; Guoliang Zhuang; Hangyu He; Siyang Liu; Shiguo Li; Junzi Li; Tingchao He; Fanghao Ye; Shuting Fan; Guijun Li (Chemical Engineering Journal, 2025)

Crop rotations reduce pathogenic fungi compared to continuous cropping - Yanhui Dou; Shuting Yu; Song Liu; Tingting Cui; Rongyan Huang; Yushu Wang; Junqiang Wang; Kefei Tan; Xinyuan Li (Rhizosphere, 2025)

STP2-mediated sugar transport in tomato shoot apices is critical for CLV3 arabinosylation and fruit locule development under low temperatures - Yimei Li; Jiao Wang; Xiao Liang; Shurong Wu; Jie Zhang; Changqi Wu; Anran Wang; Hanmo Fang; Shuting Ding; Jingquan Yu; Shuang Wu; Huan Liu; et al. (Molecular Plant, 2025)

Radical inhibition mechanisms of ammonium sulfate on industrial organic pollutants in copper-catalyzed reactions - Shuting Liu; Guorui Liu; Mingxuan Wang; Linjun Qin; Qingyu Guo; Da Li; Lili Yang; Minghui Zheng (Journal of Environmental Chemical Engineering, 2025)

Spray flame synthesis of Y2O3/Al2O3 composite nanoparticles: Effects of precursor volatility and Y/Al ratio on particle morphology and crystal phase - Shuting Lei; Yiyang Zhang; Zhu Fang; Xing Jin; Shuiqing Li (Journal of Aerosol Science, 2025)

Effects of Clitocybe squamulosa polysaccharides on the intestinal microenvironment and microbiome of cyclophosphamide-induced mice - Xueran Geng; Dongdong Guo; Guangliang Ge; Zehui Li; Shuting Hou; Tergun Bau; Sitong Yao; Lijing Xu; Yanfen Cheng; Ludan Hou; Junlong Meng; Mingchang Chang (Food Bioscience, 2025)

Magnetic field-enhanced activation of O2 by nano zero-valent iron for efficient treatment of copper-complexed wastewater - Lei Zou; Lu Wei; Yubei Liu; Mingjie Huang; Xiangling Zhang; Wenjiao Sang; Shuting Li; Chen Wang; Wei Xiang (Journal of Water Process Engineering, 2025)

Antioxidant and antimicrobial sodium alginate/sodium carboxymethyl cellulose films loaded with self-assembled hesperidin nanorods for fruits preservation - Zexin Gao; Shuting Xie; Li Chang; Huijuan Tang; Zhimin Sun; Yong Deng; Yinqi Hu; Ying Xu; Mingbao Luan (Food Chemistry, 2025)

A low-energy-consumption method simultaneously achieving rocksalt domains coating and Al-doping for Li-rich layered cathode material - Xiaoyuan Zhang; Yange Yang; Xiangnan Li; Huishuang Zhang; Hongyun Yue; Hongyu Dong; Yongfang Li; Shuting Yang; Yanhong Yin (Chemical Engineering Journal, 2025)

A global optimization method based on fuzzy clustering Kriging for aerobic wastewater treatment - Yaohui Li; Shuting Wang; Yizhong Wu; Zebin Zhang; Jingfang Shen (Journal of Environmental Management, 2025)

Genome-Wide Analysis of Ca2+-ATPases and their Salt Stress Responses in Sugar Beet - Shuting Liu; Sixue Chen; Inga R. Grin; Huizi DuanMu; Haiying Li (Sugar Tech, 2025)

Knockdown of the Clock gene in the liver aggravates MASLD in mice via inhibiting lipophagy - Shuhong Yang; Xinxin Ren; Jia Liu; Yan Lei; Minqian Li; Fang Wang; Shuting Cheng; Junjie Ying; Jie Ding; Xiaohui Chen (Molecular and Cellular Biochemistry, 2025)

Differentiating patterns of neuro-circuitry abnormalities in tremor dominant parkinson’s disease and multiple system atrophy: a resting-state fMRI study - Xiaolu Li; Huize Pang; Shuting Bu; Yingmei Li; Mengwan Zhao; Juzhou Wang; Yu Liu; Hongmei Yu; Guoguang Fan (Brain Imaging and Behavior, 2025)

ITIMCA: Image-text information and cross-attention for multi-modal cassava leaf disease classification based on a novel multi-modal dataset in natural environments - Huinian Li; Baoyu Chen; Jingjia Chen; Shuting Li; Feiyong He; Yingbiao Hu (Crop Protection, 2025)

Effects of temperature on the physicochemical properties and volatile profiles of ‘Shine Muscat’ grape during postharvest storage - Zhenghui Jiang; Xujiao Li; Shuting Peng; Xiaobei Li; Changyan Zhou; Xiaoyan Zhao (Food Chemistry, 2025)

QSAR modeling on aromatase inhibitory activity of 23 triazole fungicides by tritium-water release assay - Kun Qiao; Shuting Wang; Aoxue Wang; Zhuoying Liang; Siyu Yang; Yongfang Ma; Shuying Li; Qingfu Ye; Wenjun Gui (Environmental Pollution, 2025)

Regulating surface band structure of anisotropic SrTiO3 via ultrathin TiO2 layer to promote spatial charge separation - Shuting Zhang; Honghuo Wang; Tingting Wu; Wenjiao Chang; Yifan Li; Junying Wang; Yongqiang Yang; Lei Wang (Chemical Engineering Journal, 2025)

Distribution characteristics and influencing factors of benthic diatoms on several typical beaches along the southern coast of China - Min Chen; Jiayu Li; Guobiao Huang; Yanting Lin; Shuting Zeng; Ya Xu; Xuan Liu; Feng Cai; Hongshuai Qi (Marine Environmental Research, 2025)

Microorganism-mediated production of anthocyanins: Current progress and future prospects - Chi Shu; Shan Zhang; Siyu Wu; Shuting Liu; Jianing Xu; Jin Zhao; Bin Li (Food Research International, 2025)

Self-cleaning micro/nano graded porous groove structure fiber membranes by coaxial spinning for purification of dye wastewater - Wanwan Peng; Shuting Tian; Shuangshuang Li; Jingcheng Wu; Daqing Wu; Peng Zhou; Hongjie Li; Yi He; Yang Bai (Environmental Research, 2025)

Assessment of pollution sources and health risks of black carbon aerosols in industrial cities of Northwestern China using light absorption observations - Kai Cheng; Yuting Zhong; Xia Li; Shuting Li; Maulen Ayitken; Wang Zhang; Xinchun Liu (Atmospheric Pollution Research, 2025)

Multi-objective optimization design of double-hooked corrugated plate dryer based on NSGA-II - Zhong Shuting; Sun Rulei; Li Yang; Qin Qi; Deng Chaojun; Wang Bo; Tian Ruifeng (Annals of Nuclear Energy, 2025)

Spatial and seasonal distribution, sources, and health risks of PM2.5 loaded per- and polyfluoroalkyl substances (PFASs) in a typical megacity - Shuting Li; Guanjiu Hu; Beibei Zhang; Xuewen Yao; Zhihuai Chen; Xiaosan Luo (Science of The Total Environment, 2025)

Gallic acid reduces pericarp browning of litchi fruit during storage - Chunlan Wang; Shuting Zhang; Dandan Zhang; Fengjun Li; Lihong Xie; Tingrui Dai; Yueming Jiang (Postharvest Biology and Technology, 2025)

Identification and characterization of terpene synthase genes accounting for volatile terpene emissions in the flower of Paeonia lactiflora - Qian Zhao; Yuqing Li; Lina Gu; Shuting Li; Di He; Shanrong Dong; Qingyu Zhang; Jianrang Luo; Yanlong Zhang (Postharvest Biology and Technology, 2025)

KOH-modified biochar enhances nitrogen metabolism of the chloroquine phosphate-disturbed anammox: Physical binding, EPS modulation and versatile metabolic hierarchy - Rui Hu; Xue Chen; Yule Han; Wanjiang Li; Shuting Zhang; Zhaobin Liu; Jiandong Wang; Xueqin Lu; Gang Luo; Shicheng Zhang; Guangyin Zhen (Journal of Hazardous Materials, 2025)

Unravelling key factors controlling homogeneous crystallization during phosphorus recovery: From the perspective of crystallization kinetics - Xiang Li; Xin Hu; Shuting Shen; Rui Wan; Hongliang Dai; Xiwu Lu (Journal of Cleaner Production, 2025)

Fluorine bismaleimide resin with outstanding piezoelectric characteristics for Structure-Function integrated composites - Bilin Zhang; Fei Liu; Shuting Chen; Liangkang Huang; Yuanyuan Zhong; Wei Fan; Jianwei Li (Chemical Engineering Journal, 2025)

RIOK1/2 Negatively Regulates the Antiviral Response by Targeting TBK1 in Yellow Catfish (Pelteobagrus fulvidraco) - Kejun Liu; Jiayang Huang; Yuting Gui; Qian Li; Lei Zhang; Shuting Xiong (Fishes, 2024)
The yellow catfish (Pelteobagrus fulvidraco) industry has expanded to a certain scale and is an important part of aquaculture in China, but frequent diseases have caused huge economic losses. Comprehending the fish’s immune mechanisms, particularly the regulation of the interferon (IFN) response, is of paramount importance for future drug development and disease-resistant molecular breeding. Notably, the role of atypical protein kinases, such as the RIO kinase family, in immune regulation is poorly defined. Here, we investigated the roles of yellow catfish RIO kinases, PfRIOK1 and PfRIOK2, in modulating the IFN response through their interaction with PfTBK1, a key player in the RLR signaling pathway. Mechanically, PfRIOK1 and PfRIOK2 negatively regulate the IFN response by interacting with the RIO domains to target and degrade PfTBK1. Our findings reveal that the overexpression of PfRIOK1 and PfRIOK2 led to the decreased expression of IFN-related genes and enhanced viral replication in vitro. Additionally, PfRIOK1 and PfRIOK2 could inhibit PfTBK1-mediated antiviral responses in infected cells. These results suggest that PfRIOK1 and PfRIOK2 act as negative regulators of the IFN response in yellow catfish, providing new insights into the regulatory mechanisms of fish innate immunity and offering target molecules for molecular design breeding in aquaculture.

Associations between prenatal exposure to metal mixtures and infant reproductive hormones during mini-puberty - Ling Yu; Jiangtao Liu; Ying Li; Shulan Li; Shuting Cao; Fasheng Li; Yuanyuan Li; Hongxiu Liu; Zhenyu He; Shunqing Xu; Wei Xia (Science of The Total Environment, 2024)

Base-driven dehydrohalogenation coupled with catalytic hydrodehalogenation as a novel strategy for rapid dehalogenation of halogenated organic compounds containing aliphatic C-X bonds - Shuting Qin; Chen Wu; Xuanxuan Ma; Sujing Liu; Ying Liu; Qing Li; Bingfei Yan; Chuanhai Xia (Journal of Environmental Chemical Engineering, 2024)

Enhanced electrocatalytic performance and exceptional durability facilitate the effective degradation of m-dinitrobenzene wastewaters utilizing a novel SS/PbO2-Y2O3-SiC electrode - Haoran Wu; Qiang Yu; Huixi Li; Zhen Chen; Wei Zhu; Shuting Li; Zhengming Dai; Qichun Xi; Jinjie Wei; Tingting Li (Journal of Environmental Chemical Engineering, 2024)

Thyroid-stimulating hormone (TSH) mediates the associations between maternal metals and neurodevelopment in children: A prospective cohort study - Ling Yu; Hongling Zhang; Jiangtao Liu; Shuting Cao; Shulan Li; Fasheng Li; Wei Xia; Shunqing Xu; Yuanyuan Li (Environmental Pollution, 2024)

Elucidating the role of double-confined effect in hollow MOFs/GO catalytic membrane for deep arsenic pollution treatment - Jiangdong Dai; Lili Li; Xiaohua Tian; Ruilong Zhang; Dayi Yang; Qiaoyu Gao; Shuting Liu; Jun Zhao; Jian Ye; Xiaobo Zhang; Yi Wang (Desalination, 2024)

Fluorine polyimide nanofibrous composites with outstanding piezoelectric property for human motion monitoring - Shuting Chen; Jianwei Li; Bilin Zhang; Liangkang Huang; Keying Chen; Wei Fan; Junhao Liang (Chemical Engineering Journal, 2024)

Free radical mechanisms of ammonium sulfate as intensively used industrial materials on suppressing organic pollutants - Shuting Liu; Guorui Liu; Mingxuan Wang; Linjun Qin; Qingyu Guo; Da Li; Lili Yang; Minghui Zheng (Science of The Total Environment, 2024)

The impact of anthropogenic pressures on microbial diversity and river multifunctionality relationships on a global scale - Qian Qu; Shuting Wang; Xiangang Hu; Li Mu (Science of The Total Environment, 2024)

Urinary polycyclic aromatic hydrocarbon metabolites in Chinese pregnant women: Concentrations, variability, predictors, and association with oxidative stress biomarkers - Shuting Cao; Yanjian Wan; Yuanyuan Li; Shunqing Xu; Wei Xia (Science of The Total Environment, 2024)

Fetal weight growth trajectories and childhood development: A population-based cohort study - Xinmei Chen; Hongxiu Liu; Aifen Zhou; Feng Jin; Chufeng Jing; Yuanyuan Li; Wei Xia; Linda G. Kahn; Ya Xie; Xingliang Xiang; Shuting Cao; Wenxin Zhang; et al. (Science Bulletin, 2024)

Estimating the relationship between South China and Gondwana based on big data analysis - Zilin Zhao; Kuizhou Li; Min Deng; Ezz El Din Abdel Hakim Khalaf; Tianle Xia; Shuting Huang; Mingcai Hou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Natural enzyme cascade bimetallic sulfide MoCuSx nanozyme for synergistic photothermal/photodynamic enhanced chemodynamic antimicrobial therapy of wound infection - Caiyun Xu; Junqin Li; Chunlei Ou; Jing Yang; Shuting Fu; Weiqing Hu; Li Wang; Zefeng Wang; Luo Hai; Le Deng; Dinggeng He (Chemical Engineering Journal, 2024)

Ozone/percarbonate-Fe3+ conditioning enhanced pressurized electro-osmotic dewatering (PEOD) of waste activated sludge: Feasibility and mechanisms - Shuting Zhang; Shuxin Li; Dongqin Yuan; Qiaoyun Gao; Yili Wang; Daxin Zhang (Journal of Environmental Chemical Engineering, 2024)

Selective autophagy receptor p62/SQSTM1 inhibits TBK1-IRF7 innate immune pathway in triploid hybrid fish - Zhenghao Li; Huijuan Zhong; Shuting Lv; Yiru Huang; Shuaibin Pei; Yingbing Wei; Hui Wu; Jun Xiao; Hao Feng (Fish & Shellfish Immunology, 2024)

Heterointerface engineering of yolk-shell-structured Mn2O3/RuO2 for boosting oxygen electrocatalysis in rechargeable liquid and flexible zinc-air batteries - Xuena Ma; Mingyang Liu; ZhangXin Xu; Panzhe Qiao; Qi Li; Ruihong Wang; Shuting Zhang; Jinlong Zou; Baojiang Jiang (Chemical Engineering Journal, 2024)

Structure–activity relationship of a dual-function amine-based electrolyte for integrated CO2 capture and electrochemical conversion - Qiang Li; Tongxin Qu; Shuting Tan; Teng Wang; Yuhang Ding; Chang Wang; Junying Zhang; Zhuo Xiong; Yongchun Zhao (Chemical Engineering Journal, 2024)

Integrated transcriptome and SNP analysis reveals sex-related genetic insights in the black-spotted frog (Pelophylax nigromaculatus) - Xingyue Zhang; Gang Wan; Ziwei Li; Qiufu Wu; Shuting Xiong; Xiaoqing Wang; Lilang You; Yazhou Hu (Aquaculture International, 2024)

Bi2MoO6/MWCNTs-COOH/GCE electrochemical probe for ultrasensitively and selectively detecting antibiotic norfloxacin - Shuting Shi; Chuanqin Zhou; Aiting Chen; Nana Tang; Kun Wan; Youwei Jiang; Jun Liu; Quanguo He; Li Cao (Chemosphere, 2024)

Controllable preparation of graphene glass fiber fabric towards mass production and its application in self-adaptive thermal management - Ruojuan Liu; Fan Yang; Shuting Cheng; Xianghe Yue; Fushun Liang; Wenjuan Li; Jingnan Wang; Qinchi Zhang; Liangyu Zou; Hao Yuan; Yuyao Yang; Kangyi Zheng; et al. (Science Bulletin, 2024)

Efficient electrocatalytic OOH production on P–N–CuO for selective cleavage of lignin C–C bonds in the photoelectric collaborative system - Linglong Shi; Huifang Ma; Bin Shan; Da Li; Shuangzhen Guo; Yu Liu; Jianjie Wang; Weifang Dong; Mengqi Li; Shuting Gu; Weiyu Xia (Chemical Engineering Journal, 2024)

Future Changes in Various Cold Surges over China in CMIP6 Projections - Li Ma; Zhigang Wei; Xianru Li; Shuting Wu (Advances in Atmospheric Sciences, 2024)

Hydrogen peroxide receptors regulate chilling injury of banana fruit during low-temperature storage - Shuting Zhang; Youxia Shan; Ying Li; Junxian He; Yueming Jiang (Postharvest Biology and Technology, 2024)

Catalytic air oxidation of biogas slurry using Cu sub-nanocluster supported by mesoporous TiZrO4 and protected by SiO2 shell - Jiabai Cai; Huan Li; Wenjia Huang; Shuting He; Kai Feng; Masaki Takaoka (Journal of Hazardous Materials, 2024)

Characterization of near-field temporal and spatial variations of pesticide residues using honeybee specimens as bio-sensing matrices - Qing Cheng; Shuting Zheng; Ruisheng Wang; Chao Zeng; Kaiye Li; Chensheng Lu (Journal of Environmental Management, 2024)

Antimicrobial effect of plasma-activated water combined with tartaric acid against Staphylococcus aureus and its application on fresh-cut asparagus lettuce - Wei Wu; Jing Zhang; Tangjun Li; Zhenyang Hu; Shuting Huang; Mengshi Lin; Yunfei Xie; Zhilong Yu (Food Bioscience, 2024)

V-doping and cation-vacancy engineering synergistically promote the electrocatalysis ability of NiFe-layered double hydroxides towards the oxygen evolution and urea oxidation reactions - Huixi Li; Qiang Yu; Xingdong Zhu; Haoran Wu; Zhengming Dai; Linxia Li; Wei Zhu; Shuting Li; Zhen Chen (Chemical Engineering Journal, 2024)

Assessment of the estimation methods of Tmrt in semi-outdoor spaces in humid sub-tropical climates: An empirical study in Wuhan, China - Chuancheng Li; Kui Xu; Shuting Yan; Qunfeng Ji; Dongfang Zhang; Xilin Zhou (Building and Environment, 2024)

Soil aggregate size mediates the variations in the abundance and function of ammonia oxidizers in heavy metal-contaminated soil under different nitrogen fertilization regimes - Xian Huang; Shuting Tang; Meng Zeng; Zhongkai Qin; Jialiang Liang; Yuyuan Chen; Yamei Wu; Shuairen Chen; Fangming Yu; Yi Li (Applied Soil Ecology, 2024)

A cell-free fluorescence biosensor based on allosteric transcription factor NalC for detection of pentachlorophenol - Shuting Chen; Chen Zhao; Xiaodan Kang; Xi Zhang; Bin Xue; Chenyu Li; Shang Wang; Xiaobo Yang; Chao Li; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Biotechnology Letters, 2024)

Sediment microbial fuel cell coupled floating treatment wetland for enhancing non-reactive phosphorus removal - Shuting Shen; Longxiao Xie; Rui Wan; Xiang Li; Xiwu Lu; Hongliang Dai (Chemosphere, 2024)

Dynamic coupling between cementation and porosity evolution of the Chang 8 tight sandstone reservoir, Ordos Basin: Insights from in-situ microanalysis - Ruiliang Guo; Weiwei Yang; Xiuqin Deng; Shuting Shi; Shutong Li; Junli Qiu; Jiaqiang Zhang; Junlin Chen; Lewei Hao; Xiaofeng Ma; Dongxu Ma; Peng Liu (Marine and Petroleum Geology, 2024)

Facile fabrication of silane modified melamine sponge for highly efficient oil absorption properties - Beibei Zhang; Jin Li; Lihua Zhang; Xiutian Wang; Shuting Xie; Jiahao Quan (Journal of Water Process Engineering, 2024)

Unveiling distinct influencing mechanisms of Br- on NDMA formation during ozonation of actual water Matrixes: Identification of precursors and brominated substance - Menglan Gao; Xiaobin Liao; Shuting Chen; Xiaoying Li; Yirou Zhang; Chao Chen; Huan Qi (Chemical Engineering Journal, 2024)

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Tuning quantum dots emission on DNA tetrahedron/silica nanosphere/graphene oxide nanointerface for ratiometric fluorescence assay of Pb2+ in multiplex samples - Manting Li; Haikun Luo; Zhao Wang; Qian Mo; Shanshan Zhong; Yu-ang Mao; Shuting Li; Xinchun Li (Analytica Chimica Acta, 2024)

Trihalomethanes in global drinking water: Distributions, risk assessments, and attributable disease burden of bladder cancer - Yujie Shi; Wei Xia; Hongxiu Liu; Jiangtao Liu; Shuting Cao; Xingjie Fang; Shulan Li; Yuanyuan Li; Chao Chen; Shunqing Xu (Journal of Hazardous Materials, 2024)

The effects of different drying methods on the flavor profile of wheat germ using E-nose and GC-IMS - Yang Zhong; Gexing Zhang; Fangqin Zhang; Shuting Lin; Mei Wang; Yue Sun; Jin Liang; Xueling Li (Journal of Cereal Science, 2024)

Moisture actuated cobalt alginate discoloration artificial muscle - Chenxue Xiang; Wen Wang; Henry Ming Wang; Yangjie Huang; Lele zhang; Shuting Fang; Hao Tan; Mufang Li; Dong Wang (Chemical Engineering Journal, 2024)

Source apportionment and health risk assessment of PM2.5-bound elements on winter pollution days in industrial cities on the northern slope of Tianshan Mountain, China - Kai Cheng; Youjiang He; Yuting Zhong; Xia Li; Shuting Li; Maulen Ayitken (Atmospheric Pollution Research, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Sources and paths of extreme cold surges over China and their associated atmospheric circulations - Li Ma; Zhigang Wei; Xianru Li; Shuting Wu (International Journal of Climatology, 2024)
The extreme cold surges (ECSs) are among the extreme weather events that affect China. Here, a total of 31 ECSs that occurred from 1962 to 2018 in China were identified using observed temperature data. In addition, we used the hybrid single‐particle Lagrangian integrated trajectory (HYSPLIT) model to trace their sources. And the atmospheric circulation of ECSs with different paths were investigated. The ECSs were classified to K‐type, B‐type and S‐type ECSs (which was subdivided into the S1‐type, S2‐type and S3‐type) according to their origins and entry locations into China. The S‐type ECSs occurred the most, accounting for 58.06%. The duration and temperature drop of the K‐type ECSs were higher than those of others. And K‐type and S1‐type ECSs mainly affected Northeast China, S2‐type ECSs mainly affected the regions east of 105° E. For decadal variation, Since the 1980s, ECSs frequency has decreased (especially only one ECS occurred in the 1980s), and K‐type and S2‐type ECSs disappeared. Different types of cold surges have different atmospheric circulation characteristics. The “positive–negative–positive” wave train structures of geopotential height anomalies at 500 hPa were very conducive to the formations of K‐type, B‐type and S3‐type ECSs. For K‐type and S1‐type ECSs, the cold high gradually moved south to Siberia, and combined with the cyclone anomalies, causing the cold air to enter China. Before the B‐type ECSs occurred, cold high appeared in the west of Xinjiang, which made the southeast cold air invade China. Regarding S1‐type and S2‐type ECSs, the negative anomalies over Eurasia from day −6 to day −4 and the subsequent cyclone anomalies at 850 hPa accompanied by the southeastward extension of cold high led to ECSs.

Metal-doped alumina pellets catalyze the quick degradation of humic acid using oxygen as the oxidant at low temperatures - Shuting He; Jiabai Cai; Qi Jing; Huan Li (Journal of Water Process Engineering, 2024)

Tetracycline and sulfadiazine toxicity in human liver cells Huh-7 - Xuewen Yao; Zhaokang Cheng; Evgenios Agathokleous; Yaqian Wei; Xinyuan Feng; Hanhan Li; Tingting Zhang; Shuting Li; Gaurav Dhawan; Xiao-San Luo (Environmental Pollution, 2024)

Analysis of actual evapotranspiration changes in China based on multi-source data and assessment of the contribution of driving factors using an extended Budyko framework - Tao Su; Shuting Wang; Siyuan Sun; Taichen Feng; Bicheng Huang; Qianrong Ma; Shuping Li; Guolin Feng (Theoretical and Applied Climatology, 2024)

Mice with an autism-associated R451C mutation in neuroligin-3 show intact attention orienting but atypical responses to methylphenidate and atomoxetine in the mouse-Posner task - Shuting Li; Carlos May; Terence Y. Pang; Leonid Churilov; Anthony J. Hannan; Katherine A. Johnson; Emma L. Burrows (Psychopharmacology, 2024)

Effects of partial reduction of polystyrene micro-nanoplastics on the immunity, gut microbiota and metabolome of mice - Hua Zha; Ruiqi Tang; Shengjie Li; Aoxiang Zhuge; Jiafeng Xia; Jiawen Lv; Shuting Wang; Kaiceng Wang; Hua Zhang; Lanjuan Li (Chemosphere, 2024)

Associations between maternal urinary rare earth elements during pregnancy and birth weight-for-gestational age: Roles of cord blood vitamin D levels - Xingjie Fang; Ya Xie; Shuting Cao; Jiangtao Liu; Yujie Shi; Ling Yu; Tongzhang Zheng; Hongxiu Liu; Yuanyuan Li; Shunqing Xu; Wei Xia (Science of The Total Environment, 2024)

A facile method to construct ZIF-8 MOFs on contact lens for high antibiotics loading and self-defensive release - Yi Shao; Hao Suo; Shuting Wang; Yaou Peng; Xiaoying Chu; Ziyue Long; Kanghui Du; Lili Su; Xinyue Sun; Xinyi Wang; Qingying Wang; Renlong Li; et al. (Chemical Engineering Journal, 2024)

Environmental-friendly enzyme nanoreactors with high adsorption capacity for long-time and efficient treatment of pollutants under visible light irradiation - Shuting Huang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2024)

Roles of alcohol group in functionalized carbon nitride for photocatalytic oxidation - Shuting Feng; Xincheng Li; Xianmo Gu; Ruiyi Wang; Yunwei Wang; Zhanfeng Zheng (Fuel, 2024)

Soil aggregate size mediates the impact of different fertilization patterns on the diazotrophic community of mine soils - Xian Huang; Shuting Tang; Meng Zeng; Yamei Wu; Jialiang Liang; Yue Yuan; Fangming Yu; Yi Li (Applied Soil Ecology, 2024)

Bioleaching rare earth elements from coal fly ash by Aspergillus niger - Juanjuan Ma; Shuyan Li; Jinxi Wang; Shuting Jiang; Balaji Panchal; Yuzhuang Sun (Fuel, 2023)

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

Key geodynamic processes and driving forces of Tethyan evolution - Zhong-Hai Li; Fengyuan Cui; Shuting Yang; Xinyi Zhong (Science China Earth Sciences, 2023)

Fgf8P2A-3×GFP/+: A New Genetic Mouse Model for Specifically Labeling and Sorting Cochlear Inner Hair Cells - Yi Pan; Shuting Li; Shunji He; Guangqin Wang; Chao Li; Zhiyong Liu; Mingliang Xiang (Neuroscience Bulletin, 2023)

Effect of urban pavement on nutrient strategies of common greening tree species in northern China - Jinyan Yang; Lide Fan; Dan Song; Shuting Liu; Haifang Li; Richard Hauer; Yujie Xia; Yuwu Li (Urban Forestry & Urban Greening, 2023)

Redox-directed identification of toxic transformation products during ozonation of aromatics - Jianjian Wei; Shuting Wang; Weixu Tang; Zhourui Xu; Dehua Ma; Min Zheng; Jiansheng Li (Science of The Total Environment, 2023)

Metagenomics reveals taxon-specific responses of soil nitrogen cycling under different fertilization regimes in heavy metal contaminated soil - Xinwei Shi; Weilan Tan; Shuting Tang; Qiujie Ling; Chijian Tang; Peiqing Qin; Shiyu Luo; Yinjun Zhao; Fangming Yu; Yi Li (Journal of Environmental Management, 2023)

Vanadium dissolution restraint and conductive assistant in MnV12O31·10H2O to boost energy storage property for aqueous zinc-ion batteries - Shuting Wang; Li Xiong; Guanghui Yuan; Tao Hu; Ulla Lassi; Beibei Wang; Jintao Bai; Gang Wang; Xiujuan Wang (Chemical Engineering Journal, 2023)

Characteristics of atmospheric boundary layer and its relation with PM2.5 during winter in Shihezi, an Oasis city in Northwest China - Shuting Li; Xia Li; Zhaoze Deng; Xiangao Xia; Gang Ren; Dongliang An; Maulen Ayikan; Yuting Zhong (Atmospheric Pollution Research, 2023)

Preparation of a novel Ti/TNAs/PbO2-PVDF-Er2O3 anode by Ti3+ self-doping TNAs and its electrocatalytic performance for hydroquinone degradation - Linxia Li; Wei Zhu; Huixi Li; Shuting Li; Lei Han; Lian Ren; Meng Wang; Xia Lu; Jiali Yuan; Shutong Li; Yize Wu; Zhen Chen; et al. (Journal of Environmental Chemical Engineering, 2023)

Coupling effect analysis of drip irrigation and mixed slow-release nitrogen fertilizer on yield and physiological characteristics of winter wheat in Guanzhong area - Xin Wang; Youzhen Xiang; Jinjin Guo; Zijun Tang; Shuting Zhao; Han Wang; Zhijun Li; Fucang Zhang (Field Crops Research, 2023)

Structure and anti-inflammatory activity of neo-clerodane diterpenoids from Scutellaria barbata - ShuTing Li; Dan Xu; Jing Jia; Wenbo Zou; JieYing Liu; Yao Wang; Kun Zhang; Xi Zheng; Yan-Yan Ma; Xuejian Zhang; Deng-Gao Zhao (Phytochemistry, 2023)

Highly active complexes of pyrite and organic matter regulate arsenic fate - Shuting Wang; Jingyu Wen; Li Mu; Xiangang Hu; Ruihong Feng; Yuying Jia (Journal of Hazardous Materials, 2023)

Investigation of the effect of chemical composition of surimi and gelling temperature on the odor characteristics of surimi products based on gas chromatography-mass spectrometry/olfactometry - Wenrong Li; Li Wen; Shanbai Xiong; Shuting Xiao; Yueqi An (Food Chemistry, 2023)

N-methylpiperazine-diepoxyovatodiolide ameliorates peritoneal fibrosis via suppressing TGF-β/Smad and JAK/STAT signaling pathway - Min Mo; Yao Zeng; Yiqun Zeng; Shuting Li; Xiaoyang He; Xiaowen Chen; Qimei Luo; Mi Liu; Congwei Luo; Xianrui Dou; Fenfen Peng; Haibo Long (Chemico-Biological Interactions, 2023)

Deformation behavior and fluid action of quartz veins in the Xuelongshan metamorphic complex, Western Yunnan - Shuting Wang; Shuyun Cao; Lefan Zhan; Xuemei Cheng; Yanlong Dong; Xiaowen Li; Wenyuan Li (Science China Earth Sciences, 2023)

Lypd1-DTR/+: A New Mouse Model for Specifically Damaging the Type Ic Spiral Ganglion Neurons of the Cochlea - Di Zhang; Minhui Ren; ZhengHong Bi; Yunpeng Gu; Shuting Li; Guangqin Wang; Xiang Li; Zhiyong Liu (Neuroscience Bulletin, 2023)

Regulation of soil water and nitrate by optimizing nitrogen fertilization and the addition of manure based on precipitation: An 8-year field record - Wenguang Li; Long Ma; Fan Shi; Shuting Wang; Jiarui Zhao; Wei Zheng; Zhijun Li; Ziyan Li; Bingnian Zhai (Agriculture, Ecosystems & Environment, 2023)

Blood-based biomarkers for Alzheimer’s disease: a multicenter-based cross-sectional and longitudinal study in China - Feng Gao; Linbin Dai; Qiong Wang; Chang Liu; Kexue Deng; Zhaozhao Cheng; Xinyi Lv; Yan Wu; Ziyi Zhang; Qingqing Tao; Jing Yuan; Shiping Li; et al. (Science Bulletin, 2023)

Fabrication and characterizations of Zn-doped SnO2-Ti4O7 anode for electrochemical degradation of hexafluoropropylene oxide dimer acid and its homologues - Zehong Yang; Qiongfang Zhuo; Wenlong Wang; Shuting Guo; Jianfeng Chen; Yanliang Li; Sihao Lv; Gang Yu; Yongfu Qiu (Journal of Hazardous Materials, 2023)

Variations on the diazotrophic community in the rhizosphere soil of three dominant plant species in a lead–zinc mine area - Yi Li; Xuan Chen; Chijian Tang; Meng Zeng; Songying Li; Qiujie Ling; Kehui Liu; Jiangming Ma; Shuting Tang; Fangming Yu (Plant and Soil, 2023)

Experimental investigation of damage evolution and fracture mechanism in rocks with a single flaw under stepwise cyclic compression - Shuting Miao; Peng-Zhi Pan; Amin Hekmatnejad; Yuxin Li (Bulletin of Engineering Geology and the Environment, 2023)

Synthesis of nano-Fe3O4/ZnO composites with enhanced antibacterial properties and plant growth promotion via one-pot reaction - Xiaohui Ji; Yuanyuan Han; Yinghua Wu; Ben Liang; Jinli Zheng; Shuting Ma; Chen Li; Haitao Xu; Shaobo Guo (Environmental Science and Pollution Research, 2023)

Big-sized trees and higher species diversity improve water holding capacities of forests in northeast China - Yanbo Yang; Lixin Jing; Qi Li; Chentao Liang; Quanxing Dong; Shuting Zhao; Yuwen Chen; Danqi She; Xu Zhang; Lei Wang; Guanchao Cheng; Xiting Zhang; et al. (Science of The Total Environment, 2023)

Weibull distribution models for describing soil hydraulic properties over the entire matric suction range - Zhenlei Yang; Zi Li; Xin Tong; Shengjie Hu; Jun Wang; Shuting Ji; Ling Li (Journal of Hydrology, 2023)

Agomir miRNA-150-5p alleviates pristane-induced lupus by suppressing myeloid dendritic cells activation and inflammation via TREM-1 axis - Chenran Yue; Wenqian Wang; Sheng Gao; Jianzhong Ye; Ting Zhang; Zhouhang Xing; Yuanyuan Xie; Hengrong Qian; Xueyin Zhou; Shuting Li; Anni Yu; Liangxing Wang; et al. (Inflammation Research, 2023)

Removal of Zn2+ from glycolytic monomers of the polyethylene terephthalate based on electrodeposition - Wenxia Hou; Yi Li; Shuting Xu; Qian Wang; Kuntong Song; Junhong Liu; Nan Wang; Qing Zhou; Dongxia Yan; Xingmei Lu (Journal of Environmental Chemical Engineering, 2023)

One-pot fabrication of SF-DA@PVDF membrane for dye adsorption and oil-in-water emulsion separation - Peng Zhou; Shihong Zhang; Yi He; Jingcheng Wu; Liang Zhou; Xiangying Yin; Shuting Tian; Shuangshuang Li; Wen Chen (Journal of Environmental Chemical Engineering, 2023)

From bench to bedside: targeting lymphocyte activation gene 3 as a therapeutic strategy for autoimmune diseases - Xueyin Zhou; Yiming Gu; Huihong Wang; Wei Zhou; Lei Zou; Shuting Li; Chunyan Hua; Sheng Gao (Inflammation Research, 2023)

Shift of phytoplankton and microbial communities cause seasonal dynamics of odor compounds in Oncorhynchus mykiss cultured in a freshwater reservoir - Shuting Li; Fayi Wei; Xuan Dong; Miaojun Pan; Li Li; Xiangli Tian; Qinfeng Gao; Alan E. Wilson (Aquaculture, 2023)

The roles of exogenous ATP in postharvest fruit and vegetable: A systematic meta-analysis - Youxia Shan; Shuting Zhang; Ying Li; Jun Zhang; Mohamed A. Farag; Jun-Xian He; Jianbo Xiao; Hongxia Qu; Xuewu Duan; Yueming Jiang (Postharvest Biology and Technology, 2023)

Kinetics and capacities of non-reactive phosphorus (NRP) sorption to crushed autoclaved aerated concrete (CAAC) - Shuting Shen; Xiang Li; Zhuofan Geng; Xiwu Lu (Journal of Environmental Sciences, 2023)

An inorganic-organic-polymeric nanovehicle for targeting delivery of doxorubicin: Rational assembly, pH-stimulus release, and dual hyperthermia/chemotherapy of hepatocellular carcinoma - Jianying Yang; Zhao Wang; Chunhong Mo; Haikun Luo; Shuting Li; Qian Mo; You Qin; Fan Yang; Xinchun Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Prenatal exposure to benzotriazoles and benzothiazoles and child neurodevelopment: A longitudinal study - Shuting Cao; Jiangtao Liu; Ling Yu; Xingjie Fang; Shunqing Xu; Yuanyuan Li; Wei Xia (Science of The Total Environment, 2023)

Active species and fundamentals of their creation in Co-containing catalysts for efficient propane dehydrogenation to propylene - Yuming Li; Qiyang Zhang; Shuting Fu; Vita A. Kondratenko; Tatiana Otroshchenko; Stephan Bartling; Yaoyuan Zhang; Anna Zanina; Yajun Wang; Guoqing Cui; Mingxia Zhou; Zhen Zhao; et al. (Chemical Engineering Journal, 2023)

A review of advanced oxidation process towards organic pollutants and its potential application in fracturing flowback fluid - Xing Li; Yang Bai; Xian Shi; Shuang Chang; Shuting Tian; Meiming He; Na Su; Pingya Luo; Wanfen Pu; Zhicheng Pan (Environmental Science and Pollution Research, 2023)

Achieving phosphorus recovery at pilot-scale anaerobic anoxic/nitrifying-induced crystallization (A2N-IC) process: Performance, assessment, and challenges - Xiang Li; Shuting Shen; Zhiqiang Fu; Yiran Dong; Hongliang Dai; Xiwu Lu (Chemosphere, 2023)

Protective-mechanism-exclusive thermal stability modes of soil organic matter: Novel implication for wildfire effect on soil organic carbon - Caiqin Wang; Tingfeng Cheng; Shuting Tang; Mengxuan Li; Daoyong Zhang; Xiangliang Pan (Science of The Total Environment, 2023)

Simultaneous mitigation of arsenic and cadmium accumulation in rice grains by foliar inhibitor with ZIF-8@Ge-132 - Hao Cui; Shuting Tang; Shiqi Huang; Lidan Lei; Zhenmao Jiang; Lei Li; Shiqiang Wei (Science of The Total Environment, 2023)

Long-term effect of intermediate particulate matter (PM1–2.5) on incident asthma among middle-aged and elderly adults: A national population-based longitudinal study - Shuting Li; Jing Wei; Yaoyu Hu; Yuhong Liu; Meiling Hu; Yadi Shi; Yongxi Xue; Mengmeng Liu; Wenhan Xie; Xiuhua Guo; Xiangtong Liu (Science of The Total Environment, 2023)

Mining phosphorus from waste streams at wastewater treatment plants: a review of enrichment, extraction, and crystallization methods - Xiang Li; Shuting Shen; Yuye Xu; Ting Guo; Hongliang Dai; Xiwu Lu (Environmental Science and Pollution Research, 2023)

Affinity-based alleviation of dissolved organic matter (DOM) on tetracycline toxicity to photosynthesis of green algae Chlorella vulgaris: roles of hydrophilic and hydrophobic DOM - Caiqin Wang; Hang Xu; Tingfeng Cheng; Shuting Tang; Daoyong Zhang; Meichao Li; Xiangliang Pan (Environmental Science and Pollution Research, 2023)

A modified diatomite additive alleviates cadmium-induced oxidative stress in Bidens pilosa L. by altering soil microbial communities - Fangming Yu; Xin Liang; Yanying Li; Yanlan Su; Shuting Tang; Jiayu Wei; Kehui Liu; Jiangming Ma; Yi Li (Environmental Science and Pollution Research, 2023)

Airborne polystyrene microplastics and nanoplastics induce nasal and lung microbial dysbiosis in mice - Hua Zha; Jiafeng Xia; Shengjie Li; Jiawen Lv; Aoxiang Zhuge; Ruiqi Tang; Shuting Wang; Kaiceng Wang; Kevin Chang; Lanjuan Li (Chemosphere, 2023)

Impact of environmental factors on the ammonia-oxidizing and denitrifying microbial community and functional genes along soil profiles from different ecologically degraded areas in the Siding mine - Shuting Tang; Yin Rao; Shulian Huang; Yue Xu; Kaiyue Zeng; Xin Liang; Qiujie Ling; Kehui Liu; Jiangming Ma; Fangming Yu; Yi Li (Journal of Environmental Management, 2023)

Long-term effect of submicronic particulate matter (PM1) and intermodal particulate matter (PM1-2.5) on incident dyslipidemia in China: A nationwide 5-year cohort study - Meiling Hu; Jing Wei; Yaoyu Hu; Xiuhua Guo; Zhiwei Li; Yuhong Liu; Shuting Li; Yongxi Xue; Yuan Li; Mengmeng Liu; Lei Wang; Xiangtong Liu (Environmental Research, 2023)

Investigating multi-way impacts of transportation on human footprint: Evidence from China - Shuting Chen; Yurui Li; Zhi Lu; Rui Li; Genying Chang (Environmental Impact Assessment Review, 2023)

Effect of supply chain resilience on firm’s sustainable competitive advantage: a dynamic capability perspective - Guoli Pu; Shuting Li; Ju Bai (Environmental Science and Pollution Research, 2023)

Evolution of Meteorological Conditions during a Heavy Air Pollution Event under the Influence of Shallow Foehn in Urumqi, China - Xia Li; Keming Zhao; Shiyuan Zhong; Xiaojing Yu; Zhimin Feng; Yuting Zhong; Ayitken Maulen; Shuting Li (Advances in Atmospheric Sciences, 2023)

Effects of ocean warming and fishing on the coral reef ecosystem: A case study of Xisha Islands, South China Sea - Xinyan Zhang; Yuanchao Li; Jianguo Du; Shuting Qiu; Bin Xie; Weilin Chen; Jianjia Wang; Wenjia Hu; Zhongjie Wu; Bin Chen (Frontiers in Marine Science, 2022)
Global change has generated challenges for oceans, from individuals to the entire ecosystem, and has raised contemporary issues related to ocean conservation and management. Specifically, coral reef ecosystems have been exposed to various environmental and human disturbances. In this study, the Ecopath with Ecosim model was used to explore the impacts of ocean warming and fishing on Xisha Islands coral reef ecosystem in the South China Sea. The variables in this model included two ocean warming scenarios and three fishing scenarios. The model consisted of 23 functional groups including algae, coral, sea birds, and sharks. Our results showed that by the middle of the century, ocean warming and fishing led to a 3.79% and 4.74% decrease in total catch compared with 2009, respectively. In addition, the combined effects of ocean warming and fishing caused a 4.79% decrease in total catch, and the mean trophic level of catch was predicted to decrease by 6.01% under the SSP585-High fishing scenario. Reducing the fishing effort mitigates the effects of ocean warming on some species, such as large carnivorous fish and medium carnivorous fish; however, under low fishing effort, some functional groups, such as small carnivorous and omnivorous fish, have low biomass because of higher predation mortality.

Variation characteristics of soil temperature, moisture, and heat flux in the understorey of evergreen broadleaf forest in South China - Shuting Wu; Zhigang Wei; Xianru Li; Huan Wang; Shitong Guo (Theoretical and Applied Climatology, 2022)

Simulated warming and low O2 promote N2O and N2 emissions in subtropical montane forest soil - Xiong Yang; Yingmo Zhu; Yunjian Xu; Xiangnan Li; Shuting Zhang; Qindong Qian; Lingling Wang; Jianping Wu; Zhe Chen (Journal of Soils and Sediments, 2022)

Correction to: Root anatomical phenotypes related to growth under low nitrogen availability in maize (Zea mays L.) hybrids - Xucun Jia; Guangjun Wu; Christopher Strock; Liang Li; Shuting Dong; Jiwang Zhang; Bin Zhao; Jonathan P. Lynch; Peng Liu (Plant and Soil, 2022)

Identification of nafamostat mesylate as a selective stimulator of NK cell IFN-γ production via metabolism-related compound library screening - Qinglan Yang; Shuju Zhang; Shuting Wu; Baige Yao; Lili Wang; Yana Li; Hongyan Peng; Minghui Huang; Qinghua Bi; Peiwen Xiong; Liping Li; Yafei Deng; et al. (Immunologic Research, 2022)
Natural killer (NK) cells play important roles in controlling virus-infected and malignant cells. The identification of new molecules that can activate NK cells may effectively improve the antiviral and antitumour activities of these cells. In this study, by using a commercially available metabolism-related compound library, we initially screened the capacity of compounds to activate NK cells by determining the ratio of interferon-gamma (IFN-γ) + NK cells by flow cytometry after the incubation of peripheral blood mononuclear cells (PBMCs) with IL-12 or IL-15 for 18 h. Our data showed that eight compounds (nafamostat mesylate (NM), loganin, fluvastatin sodium, atorvastatin calcium, lovastatin, simvastatin, rosuvastatin calcium, and pitavastatin calcium) and three compounds (NM, elesclomol, and simvastatin) increased the proportions of NK cells and CD3 + T cells that expressed IFN-γ among PBMCs cultured with IL-12 and IL-15, respectively. When incubated with enriched NK cells (purity ≥ 80.0%), only NM enhanced NK cell IFN-γ production in the presence of IL-12 or IL-15. When incubated with purified NK cells (purity ≥ 99.0%), NM promoted NK cell IFN-γ secretion in the presence or absence of IL-18. However, NM showed no effect on NK cell cytotoxicity. Collectively, our study identifies NM as a selective stimulator of IFN-γ production by NK cells, providing a new strategy for the prevention and treatment of infection or cancer in select populations.

Towards economic value-added growth without carbon emission embodied growth in North–North trade—An empirical analysis of US-German trade - Rongrong Li; Shuting Ge (Environmental Science and Pollution Research, 2022)

Responses of environmental and soil enzyme stoichiometric characteristics of wheat cropping system to fertilizer management in rain-fed areas of China - Kai Wang; Lei Shi; Shuting Wang; Taotao Wang; Long Ma; Wei Zheng; Ziyan Li; Zhaohui Wang; Bingnian Zhai (Environmental Science and Pollution Research, 2022)

Root anatomical phenotypes related to growth under low nitrogen availability in maize (Zea mays L.) hybrids - Xucun Jia; Guangjun Wu; Christopher Strock; Liang Li; Shuting Dong; Jiwang Zhang; Bin Zhao; Jonathan P. Lynch; Peng Liu (Plant and Soil, 2022)

Characterization, expression, and function analysis of AKR1A1 gene from yellow catfish (Tachysurus fulvidraco) - Long Yang; Shuting Zheng; Dan Kong; Shenghan Xiang; Jianfen Wu; Neng Wan; Wenxiu Sun; Wei Li (Fish Physiology and Biochemistry, 2022)

Detection of pulmonary tuberculosis in children using the Xpert MTB/RIF Ultra assay on sputum: a multicenter study - Xiaoshan Peng; Qiong Liao; Min Fang; Yu Zhu; Yan Shi; Shuting Quan; Yacui Wang; Li Duan; Xiaomei Shi; Yang Liu; Manzhi Wang; Qingsong Wei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Sodium arsenite-mediated upregulation of circDHX34 promotes apoptosis in hormone-independent breast cancer cells by regulating apoptotic genes - Shuting Li; Chenglan Jiang; Jingwen Tan; Qian Zhou; Jinyao Yin; Yuefeng He (Environmental Science and Pollution Research, 2022)

The effects of manual airing strategies and architectural factors on the indoor air quality in college classrooms: a case study - Yanzhe Yu; Bei Wang; Shijun You; Tianzhen Ye; Wandong Zheng; Shen Wei; Shuting Yang; Yuanyuan Wang; Kun Li (Air Quality, Atmosphere & Health, 2022)

Spatiotemporal characteristics of human activity on coastal landscape of Laizhou Bay - Fan Yang; Jie Li; Jiaqing Wang; Jiantao Huang; Tong Qi; Yiman Liu; Tianyu Fu; Shuting Yu; Lingyan Zhao (Wetlands Ecology and Management, 2021)

Recent developments and applications of floating treatment wetlands for treating different source waters: a review - Shuting Shen; Xiang Li; Xiwu Lu (Environmental Science and Pollution Research, 2021)

Long-term impact of ambient air pollution on preterm birth in Xuzhou, China: a time series study - Sha Li; Lei Peng; Xiaochang Wu; Geng Xu; Peng Cheng; Jingwen Hao; Zhaohui Huang; Meng Xu; Shuting Chen; Chao Zhang; Jiahu Hao (Environmental Science and Pollution Research, 2021)

Microglial Exosome miR-7239-3p Promotes Glioma Progression by Regulating Circadian Genes - Xuepei Li; Junwen Guan; Zhou Jiang; Shuting Cheng; Wang Hou; Junjie Yao; Zhengrong Wang (Neuroscience Bulletin, 2021)
Glioma-associated microglial cells, a key component of the tumor microenvironment, play an important role in glioma progression. In this study, the mouse glioma cell line GL261 and the mouse microglia cell line BV2 were chosen. First, circadian gene expression in glioma cells co-cultured with either M1 or M2 microglia was assessed and the exosomes of M2-polarized and unpolarized BV-2 microglia were extracted. Subsequently, we labeled the exosomes with PKH67 and treated GL261 cells with them to investigate the exosome distribution. GL261 cell phenotypes and related protein expression were used to explore the role of M2 microglial exosomes in gliomas. Then a specific miR-7239-3p inhibitor was added to verify miR-7239-3p functions. Finally, the mouse subcutaneous tumorigenic model was used to verify the tumorigenic effect of M2 microglial exosomes in vivo . Our results showed that in gliomas co-cultured with M2 microglia, the expression of the BMAL1 protein was decreased ( P < 0.01), while the expression of the CLOCK protein was increased ( P < 0.05); opposite results were obtained in gliomas co-cultured with M1 microglia. After treatment with M2 microglial exosomes, the apoptosis of GL261 cells decreased ( P < 0.001), while the viability, proliferation, and migration of GL261 cells increased. Increased expression of N-cadherin and Vimentin, and decreased E-cadherin expression occurred upon treatment with M2 microglial exosomes. Addition of an miR-7239-3p inhibitor to M2 microglial exosomes reversed these results. In summary, we found that miR-7239-3p in the glioma microenvironment is recruited to glioma cells by exosomes and inhibits Bmal1 expression. M2 microglial exosomes promote the proliferation and migration of gliomas by regulating tumor-related protein expression and reducing apoptosis.

Synthesis of Multi-Functional Carbon Quantum Dots for Targeted Antitumor Therapy - Rongyao Lv; Genrong Li; Shuting Lu; Ting Wang (Journal of Fluorescence, 2021)

Arsenic exposure increased expression of HOTAIR and LincRNA-p21 in vivo and vitro - Jingwen Tan; Mingjun Sun; Quan Luo; Huiwen Sun; Mengjie Wang; Chenglan Jiang; Shuting Li; Yuefeng He (Environmental Science and Pollution Research, 2021)

Inorganic arsenic influences cell apoptosis by regulating the expression of MEG3 gene - Mengjie Wang; Jingwen Tan; Chenglan Jiang; Shuting Li; Xinan Wu; Guanghui Ni; Yuefeng He (Environmental Geochemistry and Health, 2021)

Heme oxygenase 1 plays a crucial role in swamp eel response to oxidative stress induced by cadmium exposure or Aeromonas hydrophila infection - Yuwei Zang; Shuting Zheng; Fang Tang; Long Yang; Xiping Wei; Dan Kong; Wenxiu Sun; Wei Li (Fish Physiology and Biochemistry, 2020)

Review: recent developments of substrates for nitrogen and phosphorus removal in CWs treating municipal wastewater - Shuting Shen; Xiang Li; Fangkui Cheng; Xiao Zha; Xiwu Lu (Environmental Science and Pollution Research, 2020)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

Circadian gene Clock participates in mitochondrial apoptosis pathways by regulating mitochondrial membrane potential, mitochondria out membrane permeablization and apoptosis factors in AML12 hepatocytes - Shuhong Yang; Yanyou Liu; Yimei Guo; Rong Liu; Fang Qi; Xiaoxue Li; Hang Yu; Shuting Cheng; Zhengrong Wang (Molecular and Cellular Biochemistry, 2020)

Characteristics and mechanism of dolomitization in the ooids of the Cambrian Zhangxia Formation, Xiaweidian, China - Qiheng Guo; Zhenkui Jin; Xiaoer Zhu; Shuting Shi; Junjie Wang; Jinyi Wang; Yang Li; Shuo Li (Carbonates and Evaporites, 2020)

Experimental Study on Interaction Between Degrees of Freedom in a Wave Buoy - Shuting Huang; Hongda Shi; Feifei Cao; Junzhe Tan; Haixun Cheng; Demin Li; Shangze Liu; Haoxiang Gong; Ji Tao (Journal of Ocean University of China, 2019)

EEG-based mild depression recognition using convolutional neural network - Xiaowei Li; Rong La; Ying Wang; Junhong Niu; Shuai Zeng; Shuting Sun; Jing Zhu (Medical & Biological Engineering & Computing, 2019)

Dimethylaminomicheliolide ameliorates peritoneal fibrosis through the activation of autophagy - Shuting Li; Fenfen Peng; Wangqiu Gong; Jiayu Wu; Yuxian Wang; Zhaozhong Xu; Wenting Liu; Hongyu Li; Bohui Yin; Ying Zhang; Sijia Chen; Congwei Luo; et al. (Journal of Molecular Medicine, 2019)

Transcriptome analysis of 1- and 3-year-old Panax notoginseng roots and functional characterization of saponin biosynthetic genes DS and CYP716A47-like - Jian Li; Lan Ma; Shuting Zhang; Cailian Zuo; Na Song; Shusheng Zhu; Jinsong Wu (Planta, 2019)

Land-surface temperature retrieval from Landsat 8 single-channel thermal infrared data in combination with NCEP reanalysis data and ASTER GED product - Si-Bo Duan; Zhao-Liang Li; Chenguang Wang; Shuting Zhang; Bo-Hui Tang; Pei Leng; Mao-Fang Gao (International Journal of Remote Sensing, 2019)

Interactive effects of water and controlled release urea on nitrogen metabolism, accumulation, translocation, and yield in summer maize - Guanghao Li; Bin Zhao; Shuting Dong; Jiwang Zhang; Peng Liu; Tony J. Vyn (The Science of Nature, 2017)

Production of eicosapentaenoic acid (EPA, 20:5n-3) in maize (Zea mays L.) through the alternative ∆8 desaturation pathway mediated by particle bombardment - Chenchen Wang; Xiao Yang; Haizhen Ma; Jiang Liu; Jing Chen; Jiedao Zhang; Shuting Dong; Baoxiu Qi; Xinzheng Li (Acta Physiologiae Plantarum, 2017)

The sequevar distribution of Ralstonia solanacearum in tobacco-growing zones of China is structured by elevation - Ying Liu; Dousheng Wu; Qiuping Liu; Shuting Zhang; Yuanman Tang; Gaofei Jiang; Shili Li; Wei Ding (European Journal of Plant Pathology, 2017)

Molecular characterization of heat–shock protein 90 gene and its expression in Gobiocypris rarus juveniles exposed to pentachlorophenol - Qiuping Liu; Shuting Huang; Chuan Deng; Li Xiong; Xiang Gao; Yun Chen; Chunqing Niu; Yan Liu (Fish Physiology and Biochemistry, 2015)

Comparative morphology of leaf epidermis in the genus Lithocarpus and its implication in leaf epidermal feature evolution in Fagaceae - Min Deng; Qiansheng Li; Shuting Yang; YanChun Liu; Jin Xu (Plant Systematics and Evolution, 2013)

Trends of grain yield and plant traits in Chinese maize cultivars from the 1950s to the 2000s - Xiaoke Ci; Mingshun Li; Jiashun Xu; Zhenyu Lu; Pengfei Bai; Gaolin Ru; Xiaoling Liang; Degui Zhang; Xinhai Li; Li Bai; Chuanxiao Xie; Zhuanfang Hao; et al. (Euphytica, 2012)

Effects of Developmental Exposure to TiO2 Nanoparticles on Synaptic Plasticity in Hippocampal Dentate Gyrus Area: an In Vivo Study in Anesthetized Rats - Xiaoyan Gao; Shuting Yin; Mingliang Tang; Jutao Chen; Zhongfei Yang; Wencai Zhang; Liang Chen; Bo Yang; Zhifeng Li; Yingying Zha; Diyun Ruan; Ming Wang (Biological Trace Element Research, 2011)